Preparation process of negative-electrode-free sodium metal battery and negative-electrode-free sodium metal battery

By polymerizing acrylate monomer and aromatic diamine in an anode-free sodium metal battery, the problems of sodium ion consumption and sodium dendrites are solved, and the coulomb efficiency and cycling performance of the battery are improved. High capacity and low temperature performance are achieved.

CN119208744AActive Publication Date: 2024-12-27DONGGUAN CHAM BATTERY TECH CO LTD

Patent Information

Application Number
CN202411285525.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The SEI film rupture, fast capacity decay, and low Coulomb efficiency due to the limited number of active sodium and uneven sodium ion deposition of sodium, and the lack of effective negative electrode material constraints lead to sodium dendrites growth, affecting battery performance.

Method used

Acrylate monomers and aromatic diamines are polymerized under the action of initiators to form a nitrogen-doped porous three-dimensional graphene hydrogel, which is compounded on the negative electrode current collector to form a solid electrolyte, which reduces sodium ion consumption and induces sodium crystal nuclei. The uniform formation of the battery capacity and circulation performance are improved.

Benefits of technology

It significantly improves the first Coulomb efficiency, cycle performance and low-temperature performance of the negative-node sodium metal battery, extends the battery life and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043015380000121
    Figure BDA0005043015380000121
Patent Text Reader

Abstract

The invention provides a preparation process of a negative-electrode-free sodium metal battery and the negative-electrode-free sodium metal battery. The preparation process comprises the following steps: preparing a positive plate; mixing an acrylate monomer, aromatic diamine and an initiator to obtain a first mixture, adding the graphene oxide solution, mixing to obtain a second mixture, adding a liquid electrolyte and an ether substance into the second mixture, and mixing to obtain a third mixture; separating the positive plate and the negative current collector by using an isolating membrane, assembling the positive plate and the negative current collector into a naked battery cell, packaging, filling a third mixture, and sealing; and performing formation after heating polymerization. According to the preparation process, sodium dendrites can be effectively inhibited, and the cycle performance and the low-temperature performance of the battery can be improved while the high capacity of the negative-electrode-free sodium metal battery is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a preparation process of a negative electrode-free sodium metal battery and a negative electrode-free sodium metal battery. Background Art

[0002] As the application of lithium-ion battery technology in consumer electronics, electric vehicles, energy storage and other markets gradually expands, the problem of insufficient lithium resources has also begun to emerge. Sodium-based batteries have gradually attracted attention because the earth has a sufficiently high abundance of sodium elements, and they have an important strategic position in application fields with high cost requirements such as energy storage. The large-scale application of sodium-ion batteries is limited by problems such as low specific capacity of sodium-ion batteries.

[0003] The negative electrode-free sodium metal battery does not have any sodium ion embedding material on the negative electrode side, only the negative electrode current collector, which can work as the negative terminal of the sodium metal battery after the initial charging process, thereby providing a higher operating voltage and significantly improving the volume energy density and mass energy density due to the reduction in battery volume and weight.

[0004] However, there are currently two major problems with negative electrode-free sodium metal batteries: First, due to the limited amount of active sodium in the battery, the SEI film is constantly consuming sodium ions and breaking and rebuilding as the volume of the deposited metallic sodium changes, resulting in extremely rapid capacity decay; second, in the process of repeated embedding and extraction of sodium ions, without the constraints of negative electrode materials, sodium ions are prone to uneven deposition on the current collector, resulting in "dead sodium", which affects the capacity and coulombic efficiency of the negative electrode-free battery.

[0005] Therefore, compared with electrodes with negative electrode active materials, the negative electrode current collector of negative electrode-free sodium metal batteries has a more prominent sodium dendrite growth problem, and the battery has problems such as fast capacity decay and low coulombic efficiency. Therefore, a new negative electrode current collector or negative electrode-free sodium metal battery is urgently needed to meet the needs of high capacity and high safety performance negative electrode-free sodium metal batteries, while further improving sodium dendrites, cycle and coulombic efficiency. Summary of the invention

[0006] The object of the present invention is to provide a preparation process of a negative electrode-free sodium metal battery and a negative electrode-free sodium metal battery, wherein the preparation process can effectively inhibit sodium dendrites and improve the cycle performance and low temperature performance of the battery while maintaining the high capacity of the negative electrode-free sodium metal battery.

[0007] To achieve the above object, the present invention provides a preparation process of a negative electrode-free sodium metal battery, comprising the steps of:

[0008] (1) preparing a positive electrode sheet;

[0009] (2) mixing an acrylic acid ester monomer, an aromatic diamine and an initiator to obtain a first mixture, adding a graphene oxide solution to obtain a second mixture, and adding a liquid electrolyte and an ether substance to the second mixture to obtain a third mixture;

[0010] (3) using a separator to separate the positive electrode sheet and the negative electrode current collector, assembling them into a bare cell and packaging them, injecting the third mixture and sealing them;

[0011] (4) After heating and polymerization.

[0012] In the preparation process of the negative electrode-free sodium metal battery of the present invention, acrylate monomers and aromatic diamines are polymerized under the action of an initiator and heating, and part of the acrylate monomers can reduce graphene oxide to obtain nitrogen-doped graphene as a skeleton, so that nitrogen-doped graphene hydrogel with a porous three-dimensional structure can be formed by heating polymerization and chemical formation, which can improve the low-temperature performance of the negative electrode-free sodium metal battery. Ether substances exist in the graphene hydrogel, which can be compounded on the negative electrode current collector and can form an SEI film on the surface of the current collector after chemical formation, which can reduce the consumption of sodium ions in the chemical formation stage, thereby improving the first coulomb efficiency. The nitrogen doping provided by the aromatic diamine can produce active sites, which can induce the uniform formation of sodium crystal nuclei, and also avoid the consumption of sodium ions, which can improve the capacity and cycle performance of the negative electrode-free sodium metal battery.

[0013] As a technical solution of the present invention, the acrylic ester monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate, the aromatic diamine includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA). The aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine.

[0014] As a technical solution of the present invention, the mass ratio of the acrylic ester monomer to the aromatic diamine is 1-2:1-2.

[0015] As a technical solution of the present invention, the sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the initiator is n, n / m is 0.001 to 0.010, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0016] As a technical solution of the present invention, the sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the graphene oxide solution is p, p / m is 10-90%, and the graphene oxide solution has a graphene oxide mass concentration of 1.0-5.0 mg / ml.

[0017] As a technical solution of the present invention, the mass ratio of the liquid electrolyte to the second mixture is 5-50:50-95.

[0018] As a technical solution of the present invention, the liquid electrolyte includes a sodium salt and a non-aqueous organic solvent, the sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide, and the non-aqueous organic solvent includes at least one of a carbonate, a carboxylate and a lactone.

[0019] As a technical solution of the present invention, the sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the ether substance is q, q / m is 0.01 to 0.10, and the ether substance includes at least one of dimethyl ether, tetraethylene glycol dimethyl ether and diethylene glycol diethylene dimethyl ether.

[0020] As a technical solution of the present invention, the temperature of the heating polymerization is 50 to 80° C. and the time is 4 to 9 hours.

[0021] The second aspect of the present invention provides a negative electrode-free sodium metal battery, comprising a positive electrode sheet, a separator, a negative electrode current collector and a solid electrolyte, wherein the solid electrolyte is at least composited on the surface of the negative electrode current collector. DETAILED DESCRIPTION

[0022] The negative electrode-free sodium metal battery of the present invention comprises a positive electrode sheet, a separator, a negative electrode current collector and a solid electrolyte, wherein the solid electrolyte is at least compounded on the surface of the negative electrode current collector. In other words, the solid electrolyte can be compounded on both surfaces of the separator in addition to being compounded on both surfaces of the negative electrode current collector.

[0023] The positive electrode sheet includes positive electrode active materials, positive electrode conductive agents and positive electrode binders. The positive electrode active materials include α-NaFeO2, NaCoO2, Na 0.7 [Fe 0.7 Mn 0.3 ]O2、Na(Mn 0.25 Fe 0.25 Co 0.25 Ni 0.25 )O2, NaMnO2, Na 0.5 [Fe 1 / 2 Mn 1 / 2 ]O2、Na 0.67 [Fe 1 / 2 Mn 1 / 2 ]O2, Na[Ni 0.35 Fe 0.40 Mn 0.25 ]O2, Na[Ni 0.30 Fe0.45 Mn 0.25 ]O2, Na[Ni 0.25 Fe 0.50 Mn 0.25 ]O2, Na[Ni 0.20 Fe 0.55 Mn 0.25 ]O2、Na 0.67 [Mn 0.60 Ni 0.15 Fe 0.25 ]O2、Na[Li 0.05 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.95 ]O2, Na2FePO4F, Na4Fe2(CN)6, NaNi 0.33 Fe 0.33 Mn 0.33 At least one of O2, NaFePO4, Na2FeP2O7, Na2MnPO4F, NaCoPO4, Na3V2(PO4)3, NaCrO2 and Na2Fe2(SO4)3. The positive electrode active material includes not only the above materials but also the corresponding coating and doping materials. The positive electrode conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene oxide. The positive electrode binder includes polyvinylidene fluoride. The mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder can be 90-98:1-5:1-5.

[0024] The separator is not particularly limited and may be polypropylene, polyethylene, paper, glass fiber, fiber resin, non-woven fabric, etc. The negative electrode current collector may be copper foil.

[0025] The solid electrolyte includes sodium salt and polymer electrolyte, and the polymer electrolyte is formed by polymerization of acrylate monomers and aromatic diamines and filled with graphene and ether substances. The sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium bisoxalate borate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide. The acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate. The aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The ether substance includes at least one of dimethyl ether, tetraethylene glycol dimethyl ether and diethylene glycol diethylene dimethyl ether.

[0026] The preparation process of the negative electrode-free sodium metal battery of the present invention comprises the following steps:

[0027] (1) preparing a positive electrode sheet;

[0028] (2) mixing an acrylic acid ester monomer, an aromatic diamine and an initiator to obtain a first mixture, adding a graphene oxide solution to obtain a second mixture, and adding a liquid electrolyte and an ether substance to the second mixture to obtain a third mixture;

[0029] (3) using a separator to separate the positive electrode sheet and the negative electrode current collector, assembling them into a bare cell and packaging them, injecting the third mixture and sealing them;

[0030] (4) After heating and polymerization.

[0031] In step (1), the positive electrode sheet can be a conventional all-solid-state battery sheet. The positive electrode active material, positive electrode conductive agent and positive electrode binder are mixed to form a positive electrode slurry, which is then coated on an aluminum foil, dried and rolled to obtain a positive electrode sheet. The positive electrode active materials include α-NaFeO2, NaCoO2, Na 0.7 [Fe 0.7 Mn 0.3 ]O2、Na(Mn 0.25 Fe 0.25 Co 0.25 Ni 0.25 )O2, NaMnO2, Na 0.5 [Fe 1 / 2 Mn 1 / 2 ]O2、Na 0.67 [Fe 1 / 2 Mn 1 / 2 ]O2, Na[Ni 0.35 Fe 0.40 Mn 0.25 ]O2, Na[Ni 0.30 Fe 0.45 Mn 0.25 ]O2, Na[Ni 0.25 Fe 0.50 Mn 0.25 ]O2, Na[Ni 0.20 Fe 0.55 Mn 0.25 ]O2、Na 0.67 [Mn 0.60 Ni 0.15 Fe 0.25 ]O2、Na[Li 0.05 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.95 ]O2, Na2FePO4F, Na4Fe2(CN)6, NaNi 0.33 Fe 0.33 Mn 0.33At least one of O2, NaFePO4, Na2FeP2O7, Na2MnPO4F, NaCoPO4, Na3V2(PO4)3, NaCrO2 and Na2Fe2(SO4)3. The positive electrode active material includes not only the above materials but also the corresponding coating and doping materials. The positive electrode conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene oxide. The positive electrode binder includes polyvinylidene fluoride. The positive electrode slurry is prepared by using NMP as an organic solvent. The mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder can be 90-98:1-5:1-5.

[0032] In step (2), the acrylate monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate. The aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The mass ratio of the acrylate monomer to the aromatic diamine is 1 to 2:1 to 2. As an example, the mass ratio of the two can be, but not limited to, 1:1, 1:2, 2:13:2, 3:4, 3:5, 5:3, 5:4, 2:3, 4:5. The sum of the masses of the acrylate monomer and the aromatic diamine is m, the mass of the initiator is n, and n / m is 0.001 to 0.010. As an example, n / m can be, but not limited to, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010. The initiator includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile and dimethyl azobisisobutyrate. The mass of the graphene oxide solution is p, and p / m is 10-90%. As an example, p / m can be but not limited to 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%. The graphene oxide solution is an aqueous solution with a mass concentration of graphene oxide of 1.0-5.0 mg / ml. As an example, the concentration can be but not limited to 1.0 mg / ml, 1.5 mg / ml, 2.0 mg / ml, 2.5 mg / ml, 3.0 mg / ml, 3.5 mg / ml, 4.0 mg / ml, 4.5 mg / ml, 5.0 mg / ml. The injected electrolyte includes a sodium salt and a non-aqueous organic solvent. The sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide. The non-aqueous organic solvent is selected from at least one of carbonate, carboxylic acid ester and lactone. Specifically, the non-aqueous organic solvent may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), pentylene carbonate, vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), butyl acetate (n-Ba), γ-butyrolactone (γ-Bt), propyl propionate (n-PP), ethyl propionate (EP), and ethyl butyrate (Eb). The mass ratio of the liquid electrolyte to the second mixture is 5-50:50-95. As an example, the mass ratio of the two can be but is not limited to 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:50, 50:50.The mass of the ether substance is q, and q / m is 0.01 to 0.10. For example, q / m can be, but is not limited to, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.10. The ether substance includes at least one of dimethyl ether, tetraethylene glycol dimethyl ether, and diethylene glycol diethylene dimethyl ether.

[0033] In step (3), the bare cell may be a wound cell or a laminated cell. The laminated cell is obtained by stacking a negative electrode current collector, a separator and a positive electrode sheet in sequence to obtain a laminate, and then stacking a plurality of laminates. A wound cell can be obtained by winding a single laminate. The bare cell is sealed in a packaging bag, injected with liquid, and sealed to obtain a negative electrode-free sodium metal battery precursor, and then polymerized and formed to form a solid electrolyte composited on the negative electrode current collector in the packaging bag. Since the third mixture is in a fluid state, it fills the inside of the packaging bag after injection, so the solid electrolyte formed after polymerization and formation not only exists on the surface of the negative electrode current collector, but also exists on the surface of the separator and the positive electrode sheet. However, in any case, the solid electrolyte can be composited on the negative electrode current collector. This composite structure not only solves the safety problem caused by the liquid electrolyte, but the presence of the solid electrolyte can also solve the sodium dendrite problem of the negative electrode-free sodium metal battery.

[0034] In step (4), the temperature of heating polymerization is 50-80°C. As an example, the temperature can be, but not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C. The time is 4-9h. As an example, the time can be, but not limited to, 4h, 5h, 6h, 7h, 8h, and 9h. By heating, the acrylate monomer can be polymerized with the aromatic diamine under the action of the initiator and mixed with graphene and ether to form an inorganic-organic composite solid electrolyte. Conventional chemical formation methods can be used at room temperature.

[0035] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0036] Example 1

[0037] This embodiment is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0038] (1) Preparation of positive electrode

[0039] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0040] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 1:2, and azobisisobutyronitrile accounting for 0.3 wt.% of the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a first mixture, and then a graphene oxide solution accounting for 60 wt.% of the total mass of methyl methacrylate and m-phenylenediamine (aqueous solution with a graphene oxide concentration of 5.0 mg / ml) is added and mixed uniformly to obtain a second mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 40:60, the liquid electrolyte is 1 M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 2:3. Tetraethylene glycol dimethyl ether accounts for 5% of the total mass of methyl methacrylate and m-phenylenediamine.

[0041] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0042] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0043] Example 2

[0044] This embodiment is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0045] (1) Preparation of positive electrode

[0046] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0047] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 4:5, and azobisisobutyronitrile accounting for 0.6 wt.% of the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a first mixture, and then a graphene oxide solution accounting for 60 wt.% of the total mass of methyl methacrylate and m-phenylenediamine (aqueous solution with a graphene oxide concentration of 3.0 mg / ml) is added and mixed uniformly to obtain a second mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 30:70, the liquid electrolyte is 1M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 5:3. Tetraethylene glycol dimethyl ether accounts for 10% of the total mass of methyl methacrylate and m-phenylenediamine.

[0048] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0049] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0050] Example 3

[0051] (1) Preparation of positive electrode

[0052] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0053] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 5:3, and azobisisobutyronitrile accounting for 0.9 wt.% of the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a first mixture, and then a graphene oxide solution accounting for 10 wt.% of the total mass of methyl methacrylate and m-phenylenediamine (aqueous solution with a graphene oxide concentration of 1.0 mg / ml) is added and mixed uniformly to obtain a second mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 27:73, the liquid electrolyte is 1M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 2:3. Tetraethylene glycol dimethyl ether accounts for 2% of the total mass of methyl methacrylate and m-phenylenediamine.

[0054] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0055] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0056] Example 4

[0057] (1) Preparation of positive electrode

[0058] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0059] (2) Ethyl acrylate and o-phenylenediamine are mixed in a mass ratio of 1:2, and 0.3 wt.% of azobisisoheptanenitrile is added to the mixture to obtain a first mixture, and 60 wt.% of a graphene oxide solution (aqueous solution with a graphene oxide concentration of 5.0 mg / ml) is added to the mixture to obtain a second mixture, and a liquid electrolyte and dimethyl ether are added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 40:60, and the liquid electrolyte is 0.8 M sodium hexafluorophosphate, 0.2 M sodium tetrafluoroborate and a non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC, EMC and DEC in a volume ratio of 1:2:3. Dimethyl ether accounts for 5% of the total mass of ethyl acrylate and o-phenylenediamine.

[0060] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0061] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0062] Example 5

[0063] This embodiment is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0064] This embodiment is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0065] (1) Preparation of positive electrode

[0066] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:2.5:2.5 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0067] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 1:2, and azobisisobutyronitrile accounting for 0.3 wt.% of the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a first mixture, and then a graphene oxide solution accounting for 60 wt.% of the total mass of methyl methacrylate and m-phenylenediamine (aqueous solution with a graphene oxide concentration of 5.0 mg / ml) is added and mixed uniformly to obtain a second mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 40:60, the liquid electrolyte is 1 M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 2:3. Tetraethylene glycol dimethyl ether accounts for 5% of the total mass of methyl methacrylate and m-phenylenediamine.

[0068] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0069] (4) The battery is polymerized at 70°C for 6 hours and then formed.

[0070] Comparative Example 1

[0071] This comparative example is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0072] (1) Preparation of positive electrode

[0073] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0074] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 1:2, and azobisisobutyronitrile accounting for 0.3 wt.% of the total mass of methyl methacrylate and m-phenylenediamine is added and mixed to obtain a first mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the first mixture to obtain a second mixture. The mass ratio of the liquid electrolyte to the first mixture is 40:60, the liquid electrolyte is 1M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 2:3. Tetraethylene glycol dimethyl ether accounts for 5% of the total mass of methyl methacrylate and m-phenylenediamine.

[0075] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the second mixture and sealing them.

[0076] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0077] Comparative Example 2

[0078] This comparative example is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0079] (1) Preparation of positive electrode

[0080] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0081] (2) Methyl methacrylate and m-phenylenediamine are mixed in a mass ratio of 1:2, and 0.3 wt.% of azobisisobutyronitrile accounting for the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a first mixture, and then 60 wt.% of a graphene oxide solution (aqueous solution with a graphene oxide concentration of 5.0 mg / ml) accounting for the total mass of methyl methacrylate and m-phenylenediamine is added and mixed uniformly to obtain a second mixture, and a liquid electrolyte is added to the second mixture to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 40:60, the liquid electrolyte is 1M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC in a volume ratio of 2:3.

[0082] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0083] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0084] Comparative Example 3

[0085] This comparative example is a preparation process of a negative electrode-free sodium metal battery, which includes the following steps.

[0086] (1) Preparation of positive electrode

[0087] The highest charging voltage is 4.2V. 0.30 Fe 0.45 Mn 0.25 ]O2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 96:1:3 to form a positive electrode slurry with a certain viscosity. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0088] (2) Azobisisobutyronitrile accounting for 0.3 wt.% of the mass of methyl methacrylate is added to methyl methacrylate and mixed evenly to obtain a first mixture, and then a graphene oxide solution accounting for 60 wt.% of the mass of methyl methacrylate (aqueous solution with a graphene oxide concentration of 5.0 mg / ml) is added and mixed evenly to obtain a second mixture, and a liquid electrolyte and tetraethylene glycol dimethyl ether are added to the second mixture and mixed to obtain a third mixture. The mass ratio of the liquid electrolyte to the second mixture is 40:60, the liquid electrolyte is 1M sodium hexafluorophosphate + non-aqueous organic solvent, and the non-aqueous organic solvent is a mixed solvent of EC and EMC with a volume ratio of 2:3. Tetraethylene glycol dimethyl ether accounts for 5% of the mass of methyl methacrylate.

[0089] (3) Using an isolation film to separate the positive electrode sheet and the copper foil, assembling them into a bare cell and then packaging them, pouring the third mixture and sealing them.

[0090] (4) The battery was polymerized at 75°C for 9 hours and then formed.

[0091] The electrochemical performance of the negative electrode-free sodium metal batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested under the following test conditions. The test results are shown in Table 1.

[0092] (1) First Coulomb efficiency test

[0093] The negative electrode-free sodium metal battery is subjected to aging, formation, sealing, and capacity division steps according to conventional means, wherein the charging capacity during the formation process is recorded as C1, the charging capacity during the capacity division process is recorded as C2, and the discharge capacity during the capacity division process is recorded as C0.

[0094] First coulomb efficiency = C0 / (C1+C2)×100%

[0095] (2) Normal temperature cycle performance test

[0096] A negative electrode-free sodium metal battery was placed in an environment of 25°C, charged at a constant current of 1C to 4.0V, then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to 2.0V. This cycle was repeated for 500 cycles, and the discharge capacity of the first cycle and the last cycle were recorded. The capacity retention rate of the room temperature cycle was calculated according to the following formula.

[0097] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%

[0098] (3) Low temperature performance test

[0099] At room temperature (25°C), the negative electrode-free sodium metal battery was charged and discharged at 0.05C / 0.05C (the battery discharge capacity was recorded as C0), with an upper voltage of 4.0V. The battery was then placed in a low-temperature box at -10°C, and then discharged at a constant current of 0.1C to a voltage of 2.0V. The first discharge capacity of the battery was recorded. This was a charge and discharge cycle. The battery was disassembled after 10 cycles and the capacity retention rate was calculated.

[0100] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%

[0101] Table 1 Electrochemical performance test results of Examples 1 to 5 and Comparative Examples 1 to 3

[0102]

[0103] From the results in Table 1, it can be seen that the use of acrylic acid ester monomers and aromatic diamines for polymerization, and then forming nitrogen-doped graphene hydrogels with porous three-dimensional structures with graphene, ether materials, and liquid electrolytes, which are compounded on the negative electrode current collector, can make the prepared negative electrode-free sodium metal battery have a higher first coulomb efficiency, better cycle performance and low-temperature performance. This is because the porous three-dimensional structure of the graphene hydrogel can improve the low-temperature performance of the negative electrode-free sodium metal battery. The ether material can form an SEI film on the surface of the current collector after being compounded on the negative electrode current collector and then formed, which can reduce the consumption of sodium ions in the formation stage, thereby improving the first coulomb efficiency. The nitrogen doping provided by the aromatic diamine can produce active sites, which can induce the uniform formation of sodium crystal nuclei and avoid the consumption of sodium ions, which can improve the capacity and cycle performance of the negative electrode-free sodium metal battery.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A preparation process for a negative electrode-free sodium metal battery, characterized in that: Includes steps: (1) preparing a positive electrode sheet; (2) mixing an acrylic acid ester monomer, an aromatic diamine and an initiator to obtain a first mixture, adding a graphene oxide solution to obtain a second mixture, and adding a liquid electrolyte and an ether substance to the second mixture to obtain a third mixture; (3) using a separator to separate the positive electrode sheet and the negative electrode current collector, assembling them into a bare cell and packaging them, injecting the third mixture and sealing them; (4) After heating and polymerization.

2. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The acrylic acid ester monomer includes at least one of methyl methacrylate, ethyl methacrylate, methyl acrylate and ethyl acrylate, and the aromatic diamine includes at least one of o-phenylenediamine, m-phenylenediamine and p-phenylenediamine.

3. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The mass ratio of the acrylic ester monomer to the aromatic diamine is 1-2:1-2.

4. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the initiator is n, n / m is 0.001-0.010, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

5. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the graphene oxide solution is p, p / m is 10-90%, and the graphene oxide solution is an aqueous solution with a graphene oxide mass concentration of 1.0-5.0 mg / ml.

6. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The mass ratio of the liquid electrolyte to the second mixture is 5-50:50-95.

7. The preparation process of the negative electrode-free sodium metal battery according to claim 1, characterized in that: The liquid electrolyte includes a sodium salt and a non-aqueous organic solvent, wherein the sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide, and the non-aqueous organic solvent includes at least one of carbonate, carboxylate and lactone.

8. The process for preparing a negative electrode-free sodium metal battery according to claim 1, characterized in that: The sum of the masses of the acrylic ester monomer and the aromatic diamine is m, the mass of the ether substance is q, q / m is 0.01-0.10, and the ether substance includes at least one of dimethyl ether, tetraethylene glycol dimethyl ether and diethylene glycol diethylene dimethyl ether.

9. The process for preparing a negative electrode-free sodium metal battery according to claim 1, characterized in that: The temperature of the heating polymerization is 50-80° C. and the time is 4-9 hours.

10. The negative electrode-free sodium metal battery prepared by the process for preparing a negative electrode-free sodium metal battery according to any one of claims 1 to 9, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode current collector and a solid electrolyte, wherein the solid electrolyte is at least compounded on the surface of the negative electrode current collector.

Citation Information

Patent Citations

  • Graphene compound and manufacturing method thereof, electrolyte, and power storage device

    CN107963969A

  • Negative-electrode-free ether high-voltage sodium secondary battery and preparation method thereof

    CN114464873A

  • Sodium-philic 3D carbon current collector, preparation method and application thereof, and preparation method of negative-electrode-free solid-state sodium battery

    CN115064702A

  • Solid polymer electrolyte, preparation method thereof and application of solid polymer electrolyte in secondary battery

    CN117673461A

  • Stethoscope type thermometer

    KR1020240173831A

Cited By

  • Modified diaphragm applied to low-temperature negative-electrode-free sodium metal battery as well as preparation method and application of modified diaphragm

    CN119965463A